Bloodline - Acosta, Amabel Anne M.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
Parents are a child's first teachers. They are the ones who teach a child his first word, his first step and how to do things on his own for the first time. They teach the child how to tie his shoes, use the toilet bowl, sing a nursery rhyme, and recite the alphabet. Parents are a child's highest authority. This is not only part of our culture, but it is taught by religion as well -- children should obey and honor their parents. Parents are said to know better than the children do. They are said to know what is right from wrong. Parents are a child's greatest influence. Being the first people that a child sees during his formative years, parents have a greater hold on their children than anyone else does. During his early years of development, his parents are his only role models. This will be a stylized film using red, white and black as the dominant colors. In this firm, red is the representation of the blood relation between the main characters in the film. Yet, they will be seen dressed in white. While in the representation of nothingness, a state where one is free from connection and obligation from other people, even their family. Black is the representation of impurity. The filmmaker's use of the fourth commandment -- "Honor thy father and thy mother." - as a repeating voice-over is a representation of the influence of religion on the notion that parents should teach children and children should follow their parents more than anyone else. It is taught by religion, whether Catholic or not, that disobedience is man's greatest sin to his parents. The cigarette is not only used a technique for continuity; it is shown as a form of outlet from stress, frustration and dissatisfaction for the characters in the film. The use of the fish in a bowl is a representation of being trapped in a small space where standards of his parents and being limited to the norms of the society, particularly to obedience to parents. The pollution of the water in the bowl is a representation of the child's rebellion and misbehavior. The killing of the fish is a representation of the child's desire to escape. The parents' inability to recognize their child's dilemma led the child to eventually become like her parents. At the end of the film, it is revealed that she will treat her child the same as her parents have treated her. This is a 12-minute experimental shot and edited on digital video.
Vita.
Thesis (A.B. Film and Audiovisual Communication)--University of the Philippines Diliman
Keywords: Bloodline (Short films -- Philippines).; Parent-adult child relations -- Philippines).